PENGARUH BRAND AMBASSADOR DEDDY CORBUZIER DAN BRAND AWARENESS TERHADAP MINAT GENERASI Z DALAM BERINVESTASI DI BIBIT - Budi Rustandi Kartawinata; Treshya Setya Maharani (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
In this increasingly modern era, technological developments are advancing and developing, as is the case with the investment sector. In the past, investing only focused on conventional investment matters, but now it's getting easier with various advances from investment companies. The development of investors in Indonesia is growing rapidly and showing a positive trend, which means that the investment awareness of the Indonesian people is getting better and starting to invest slowly. Seeds is an investment application whose users are dominated by Generation Z. Awareness of investment by young people is getting higher and of course this will reduce the financial gap that exists and the economy in Indonesia. In marketing, Seeds uses a digital marketing strategy, one of which is making Deddy Corbuzier a brand ambassador. The purpose of this study is to determine the influence of brand ambassadors and brand awareness on investment interest in Seeds. The method used in this research is to use quantitative research methods with descriptive research types. The population used in this study, namely the people of West Java aged 15-25 years and using the Seeds application with a total sample of 100 respondents. Sampling used in this research is purposive sampling method. Based on the results of the study using descriptive analysis with the help of SPSS for windows software, it shows that brand ambassadors and brand awareness have a significant effect simultaneously and partially on investment interest in Seeds. Keywords: Brand Ambassador, Brand Awareness, Investment Interest